Awareness Regarding Cyberbullying among Adolescents of Selected Schools of Mechinagar Municipality, Jhapa (The Journal of Knowledge and Innovation, 2024)
Cyberbullying is harassing, insulting, physically threatening, socially excluding and humiliating other using electronic media such as E-mail, internet site, instant internet messaging and cell phone text messages. High school and college students continue to be the population that utilizes the internet and social media most often including email, cell phones, instant messaging, and chat rooms. So, these populations are at high risk of cyber bullying. The main objective of this study is to find out the level of awareness regarding cyberbullying among adolescent’s students of Mechinagar Municipality.A cross-sectional study was conducted to assess the level of awareness regarding cyberbullying by using non-probability purposive sampling technique among adolescent’s students of grade 9 and 10 of two secondary schools of Jhapa through a self-administered questionnaire method. Data was entered in the SPSS version 21 and data analysis was done using descriptive statistics like mean, median, frequency, percentage and standard deviation. Inferential statistics chi-square test was used to show association between cyberbullying and selected socio-demographic variables.The findings of the study concluded that out of 400 respondents, more than one-third of the participants had a low level of awareness of cyberbullying, more than two-fifth had a moderate level of awareness, and least number of participants had a high level of awareness. There was significant association between level of awareness on cyberbullying with parental education and father’s occupation.